Institute of sovereign welfare funds: safety aspects and economic and legal principles - Karapetian, Olha (Actual problems of law (Aktual’ni problemi pravoznavstva), 2020)
The article looks at the activities of the largest sovereign wealth funds and analyzes the functions, tasks and risks associated with the activities of sovereign wealth funds. The questions of motivation of such funds, their influence on the main participants of the financial market in the context of impact on economic security are raised. It is argued that at the turn of the fourth scientific and technological revolution, it is necessary to pay attention to the long-standing experience of managing the state reserves in order to determine the main tendencies of development of sovereign funds. In addition, particular attention was paid to quantifying the impact of a variety of economic factors on the functioning of sovereign wealth funds. The article describes the main development trends and problems of functioning of the largest sovereign wealth funds in the world. Attention is paid to the key problems of functioning of sovereign wealth funds and the main risks of their activity are identified. The organizational and legal principles of the formation of sovereign wealth funds are defined and the perspective directions for improving their activities are outlined. It is argued that at the turn of the fourth scientific and technological revolution, it is necessary to pay attention to the long-standing experience of managing the state reserves in order to determine the main tendencies of development of sovereign funds. In addition, particular attention was paid to quantifying the impact of a variety of economic factors on the functioning of sovereign wealth funds. The article describes the main development trends and problems of functioning of the largest sovereign wealth funds in the world. Attention is paid to the key problems of functioning of sovereign wealth funds and the main risks of their activity are identified. The organizational and legal principles of the formation of sovereign wealth funds are defined and the perspective directions for improving their activities are outlined.